Study of vulnerability to contamination of the Ribeirão Claro hydrographic basin's northern portion, SP, Brazil - De Sisto, Felipe Pereira [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; Do Carmo Giordano, Lucilia [UNESP]; De Oliveira, Alan [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2018)
Because it is an unconfined aquifer and is relatively close to the surface, Rio Claro Aquifer becomes an easy target for infiltration of contaminants from various sources. The present paper aims to study the vulnerability of the upper layers of the soils on the Ribeirão Claro hydrographic basin's north section. A contamination vulnerability map was created, relating the geology and the use and occupation of the soil in the area. Furthermore, in situ geotechnical testing was performed using the Guelph Permeameter, alongside with the collect of deformed and undeformed soil samples of the Rio Claro Formation, in order to perform laboratory geotechnical testing and obtain material physical parameters and its grain size, as well as its sedimentation rate. With the obtained results, it can be concluded that the hydraulic conductivity of the Rio Claro Formation's soils is heterogeneous, a reflex of its composition. The contamination vulnerability for the aquifer area obtained in this paper is, in general, high.
Estudo da vulnerabilidade à contaminação na porção norte da Bacia Hidrográfica do Ribeirão Claro, SP
Keywords: Geotechnical testing; Hydraulic conductivity; Rio Claro Aquifer; Vulnerability